Time-dependent study of quantum transport and dissipation - Zhang, Yu (The University of Hong Kong (Pokfulam, Hong Kong), 2014)
Dissipative time-dependent quantum transport theory with electron-phonon interaction in either weak or strong coupling regime is established. This theory goes beyond the conventional quantum master equation method and Kadanoff-Baym kinetic equations. It provides an efficient method for the simulation of transient quantum transport under arbitrary bias voltage with different electron-phonon coupling strength.